Assessment of Subclinical Cardiovascular Disease Risk by Measuring Carotid Intima Media Thickness in Rheumatoid Arthritis Patients: A Cross-sectional Study - Tamanna Singh; Manaswi Chaubey; Ranjan Bhattnagar; Niharika Mayank; Aditya Debuka (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Rheumatoid Arthritis (RA) is a chronic inflammatory disease that affects both synovial joints and extra-articular regions. Patients with RA have an increased risk of Cardiovascular Disease (CVD), leading to premature mortality. Aim: To assess subclinical atherosclerosis in RA patients using Carotid Intima Media Thickness (CIMT) and compare it with age-matched healthy individuals. Materials and Methods: This cross-sectional study included 50 RA patients and 50 healthy age- and sex-matched controls. Ultrasound was used to measure CIMT, which serves as an indicator of subclinical atherosclerosis. Framingham, Atherosclerotic CVD (ASCVD) risk scores, and QRISK3 scores were used to estimate the 10-year CVD risk. Student’s t-test and Chi-square test were used to identify statistically significant differences. Results: RA patients had significantly higher mean CIMT values compared to controls (p-value<0.001), indicating an increased burden of atherosclerosis. While ASCVD scores were comparable, Framingham scores were significantly lower (p-value=0.028), and QRISK3 scores were significantly higher (p-value=0.007) in RA patients. This suggests an underestimation of CVD risk by Framingham and potentially better prediction by QRISK3. Conclusion: The study highlights that RA patients have a higher burden of atherosclerotic disease compared to healthy adults of the same age when CIMT is used as a marker of atherosclerosis. These findings indicate the need for early CVD risk assessment and intervention in RA patients using appropriate risk-scoring systems and tools. Further research with larger sample sizes and longitudinal follow-up is warranted to confirm these findings.